Observasi Klinik Ramuan Jamu untuk Menurunkan Berat Badan - Pamadyo(, Sunu; Novianto, Fajar; Mujahid, Rohmat (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2015)
The prevalence of overweight (obesity) has increased significantly in the world. During this decade, obesity will become a health problem. Even today, obesity is referred to as the New World Syndrome, where it is continuity increasing the number of events almost all over the world. Based on Riskesdas in 2010, the prevalence of adult obesity in Indonesia had reached 21.7%, significantly increasing if it was compared to the previous Riskesdas in 2007 which were 10.3%. Obesity in the younger people was associated with the increased of the incident risk of coronary heart disease, hypertension, hypercholesterolemia, diabetes mellitus and metabolic disorders. Obesity has a strong correlation with morbidity and mortality, and received serious attention on the causes, prevention and treatment efforts. Until now, there has been no specific drugs used for weight loss. People saw fitoterapi as a weight loss (besides diet)drug, because it has been considered relatively safe and without significant side effects. Jamu consisting of Jati Belanda, Kemuning, Kelembak and tempuyung was used in Saintifikasi Jamu Clinic. The results in this jamu showed that capsule weight loss has gave lower Body Mass Index (BMI) for 2 months but it has not lowered the BMI category of overweight to normal. The jamu could significantly reduce the weight of research subyek after administration for 28 days, with an average decline of 3.9 Kg and a highly significantly decrease after 56 days administration, with an average decrease of 6.7 Kg, compared to the initial weight. Medicinal herb could reduce the waist 41.1 cm, after 56 days administration. The herbs could not reduce the upper arm circumference, after 56 days administration.